Angiographic determinants for side branch treatment in distal unprotected left main coronary artery bifurcation percutaneous coronary intervention with single stent crossover technique - Bhupal, V. S. R.; Kumar, P. Sampath (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this study was to analyze angiographic parameters such as bifurcation angle, diameter at the polygon of confluence (POC) and SYNTAX score in predicting the need for side branch treatment with single-stent crossover technique from distal unprotected left main coronary artery (ULMCA) to the major side branch. Methods: This was a retrospective and observational study. A total of 83 patients with distal ULMCA lesions were enrolled. Patients who underwent provisional single-stent crossover technique were compared with patients that required side branch treatment though plain old balloon angioplasty (POBA) 5 (6.0%) or stenting 7 (8.4%). Angiographic parameters, bifurcation angle, diameter at the POC and the SYNTAX score were analyzed for their ability to predict the need for side branch treatment. Results: Mean age of patients was 58.2±5.3 years. Males constituted 61 (73.5%) patients. Post main branch stenting 5 (6.0%) and 7 (8.4%) patients required side branch treatment with POBA and stent implantation, respectively. Binary regression revealed bifurcation angle (Z: 1.15, OR: 0.99, 95% CI: 0.97-1.01, p=0.25), diameter at the POC (Z: 1.1, OR: 0.82, 95% CI: 0.32-2.13, p=0.272) and SYNTAX score (Z: 1.51, OR: 1.18, 95% CI: 0.95-1.45, p=0.132) did not correctly predict the requirement of side branch treatment. Conclusion: Left main coronary artery to main branch stenting can be performed safely with single-stent crossover technique, irrespective of presence of side branch disease across a wide range of bifurcation angles, diameters at the POC and SYNTAX scores.